Development of Enriched Core Competencies for Health Services and Policy Research. (11th March 2018) - Bornstein, Stephen; Heritage, Melissa; Chudak, Amanda; Tamblyn, Robyn; McMahon, Meghan; Brown, Adalsteinn D.
Abstract : Objective: To develop an enriched set of core competencies for health services and policy research (HSPR) doctoral training that will help graduates maximize their impact across a range of academic and nonacademic work environments and roles. Data Sources/Study Setting: Data were obtained from multiple sources, including literature reviews, key informant interviews, stakeholder consultations, and Expert Working Group (EWG) meetings between January 2015 and March 2016. The study setting is Canada. Study Design: The study used qualitative methods and an iterative development process with significant stakeholder engagement throughout. Data Collection/Extraction Methods: The literature reviews, key informant interviews, existing data on graduate career trajectories, and EWG deliberations informed the identification of career profiles for HSPR graduates and the competencies required to succeed in these roles. Stakeholder consultations were held to vet, refine, and validate the competencies. Principal Findings: The EWG reached consensus on six sectors and eight primary roles in which HSPR doctoral graduates can bring value to employers and the health system. Additionally, 10 core competencies were identified that should be included or further emphasized in the training of HSPR doctoral students to increase their preparedness and potential for impact in a variety of roles within and outside of traditional academic workplaces. Conclusion: The results offer an expanded view of potential career paths for HSPR doctoral graduates and provide recommendations for an expanded set of core competencies that will better equip graduates to maximize their impact on the health system.